Enhanced Expectancies Improve Performance Under Pressure - McKay, Brad; Lewthwaite, Rebecca; Wulf, Gabriele (Frontiers in Psychology, 2012)
Beyond skill, beliefs in requisite abilities and expectations can affect performance. This study examined effects of induced perceptions of ability to perform well under generic situations of challenge. Participants (N = 31) first completed one block of 20 trials on a throwing accuracy task. They then completed questionnaires ostensibly measuring individual differences in the ability to perform under pressure. Enhanced-expectancy group participants were told that they were well-suited to perform under pressure, while the control group received neutral information. Subsequently, all participants completed another block of 20 trials on the throwing task, with their performance being videotaped and under the assumption that they could secure a prize for themselves and a paired participant with successful performance. Both groups had similar accuracy scores on the first trial block. The enhanced-expectancy group significantly increased their throwing accuracy in the high-pressure situation (second block), whereas the control group showed no change in performance. Furthermore, beliefs regarding performance under challenge predicted throwing accuracy on the second block. The present findings provide evidence that enhancing individuals’ generic expectancies regarding performance under pressure can affect their motor performance.